CRIMINAL LEGAL RESPONSIBILITY FOR THE USE OF NURSING PERSONNEL IN ANESTHESIA SERVICES: A LEGAL ANALYSIS FROM THE PERSPECTIVE OF LAW NUMBER 17 OF 2023 CONCERNING HEALTH - Bahrun Sihotang; Moh. Lubsi Tuqo Romadhan (PT. Radja Intercontinental Publishing, 2026)
The use of nursing staff in anesthesia services has become a common practice in various Indonesian healthcare facilities. However, the arrangement of authority between